What opinions do Saudi endodontic residents hold about regenerative endodontics? - Saeed S Al Qahtani; Salman Aziz; Hmoud Al Garni; Mohammed Sulmain Alaenazi (Saudi Endodontic Journal, 2019)
Aim: The aim of this study is to investigate the opinions, current knowledge, and expectations of Saudi endodontic residents regarding the use of regenerative endodontics as part of future dental treatment and establishing a baseline for further research and development. Materials and Methods: Saudi endodontic residents all over Kingdom of Saudi Arabia (KSA) were contacted, for participation. A survey form consisting of 28 questions was personally distributed to all endodontic residents who were actively enrolled in a residency training program either Saudi board program or Master Degree and provided informed consent for inclusion into the study. Data were collected and statistical analysis was carried out using SPSS version 22. Results: Out of one hundred and fifteen endodontic residents 97 participated in this questionnaire-based survey. Two forms were excluded due to incomplete and unclear information. Out of the remaining 95 majority of the residents were male (67.4%) and belonged to Saudi board program. The greater part of residents agreed for the inclusion of regenerative endodontics in the dental curricula. Most of the candidates wanted to improve their skills in regenerative endodontics by participating in continuing dental education programs. The most popular belief (n = 81) was that regenerative therapy to save teeth is better than implants. Use of regenerative procedures in clinics was carried out by only 44 participants. Conclusion: The emerging importance of regenerative endodontics in KSA is evident through this study. This study highlights many core issues which need attention and forms a baseline for further research in regenerative endodontics.